The Effect of Rural Residence on Cancer‐Related Self‐Efficacy With UK Cancer Survivors Following Treatment. Issue 1 (2nd December 2020) - Nelson, David; Law, Graham R.; McGonagle, Ian; Turner, Paul; Jackson, Christine; Kane, Ros
Abstract: Purpose: To examine rural and urban differences in cancer‐related self‐efficacy with UK cancer survivors following treatment. Methods: A cross‐sectional postal survey with posttreatment cancer survivors in the East Midlands of England. The survey collected data on demographics and cancer‐related self‐efficacy using the Cancer Survivors Self‐Efficacy Scale. Rural‐urban residence was determined using Office for National Statistics classifications. Linear Regression models were developed using a Directed Acyclic Graph that determined confounding variables. When the model deviated from normal the outcome variable was transformed using the Box‐Cox transformation. Findings: Of those surveyed, 227 responded, of whom 58% were female and 45% lived in a rural area. A linear regression model showed a significant increase in cancer‐related self‐efficacy in cancer survivors living in rural areas compared to urban residents (0.76, 95% CI: 0.25‐1.27), although the residual plot deviated from a normal distribution. A model of the effect of rural living on a Box‐Cox transformed outcome variable confirmed an increased cancer‐related self‐efficacy score in rural regions (9.06, 95% CI: 2.97‐15.14). Rural living remained significant (7.98, 95% CI: 1.78‐14.19) after adjustment for the respondents' income. Similarly adjusting for deprivation led to a significant increase in cancer‐related self‐efficacy in rural regions (8.64, 95% CI: 2.48‐14.79). Conclusion: This study has important implications when considering the impact of location of residence on cancer‐related self‐efficacy in cancer survivorship. The role of deprivation had some impact for sample respondents in both the urban and rural environment and merits further analysis.